Comparative impact of invasive alien trees and vineyards on arthropod diversity in the Cape floristic region, Western Cape - Magoba, Rembuluwani Norman Nicholas (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Conservation Ecology and Entomology))--University of Stellenbosch, 2010.